Perspektif Pancasila dalam Mewujudkan Kesetaraan Digital sebagai Upaya Menuju Good Governance - Khansa Amani; Fatma Ulfatun Najicha (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2024)
The rapid development of Information and Communication Technology (ICT) urges both society and the state to adapt swiftly. Technology has altered various aspects of life and offers conveniences. However, a segment of the Indonesian populace is experiencing a digital divide due to this rapid advancement. The digital gap is propelled by geographic factors, unequal infrastructure, motivation, skills, aims, and perceived impacts. This digital discrepancy brings forth various detrimental effects on the populace. It impedes the Government's efforts to achieve good governance and prosperity for Indonesian society. Pancasila, as the foundation of the Indonesian state, encapsulates values of justice, aspiring for equality among Indonesians across various domains. The existence of a digital divide contradicts these aspirations. The digital gap contradicts the ideals of Pancasila, and thus, Pancasila can serve as a basis and guide in addressing this issue. The values within Pancasila can be utilized as a foundation in devising strategies to bridge the digital divide and create digital equality. Keywords: Digital divide, Pancasila, Digital equity, Good governance